The Effect of Implementing the Android-Based Jire Collaborative Learning Model on Momentum and Impulse Materials to Improve Student Learning Outcomes - Nova Elysia Ntobuo; Lanto Mohamad Kamil Amali; Dewi Diana Paramata; Muhammad Yunus (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect of applying the android-based Jire collaborative learning model on momentum and impulse material to improve student learning outcomes. The research method is a quasi-experimental design with a one-group pretest-posttest research design. The research location at SMA Negeri 6 Gorontalo Utara for the 2021/2022 academic year used four research samples, namely class X IPA 1 as the experiment class and class X IPA 2, X IPA 3, and X IPA 4 as the replica class. This research begins with the preparation of learning tools that physics learning experts and learning media experts validate. The results of the validation show that the learning tools are valid and can be used in the learning process. The implementation of the learning process in this study is in the excellent category and can improve student learning outcomes. The N-Gain value for the experimental class and replica class is in the high category. Student responses to using the android-based Jire collaborative learning model show good and excellent categories. This shows that the Jire collaborative learning model can be used to improve student learning outcomes in physics learning